Taxonomia integrativa e biogeografia dos cascudinhos da subfamília Hypoptopomatinae (Siluriformes: Loricariidae) do Nordeste do Brasil - Barros Neto, Luciano de Freitas (2020)
The Northeastern region of Brazil, which includes five distinct hydrographic ecoregions, is suitable for river captures mainly because of lithological and geological characteristics as well as successive fault reactivation phases. However, the biogeographic history of neotropical watersheds in this region remains poorly understood despite their high levels of fish endemism. The genus Parotocinclus presents high number of endemic species in the region, with some species with distribution restricted to a single basin, while others with wider distributions, occurring in more than one ecoregion. In this sense, unravelling the evolutionary history of the genus Parotocinclus can help elucidate the historical processes that influenced the genetic variation of freshwater fish in these coastal basins. However, the validity of some species is questioned. Moreover, most of the species descriptions for the genus are little informative, and do not present diagnostic characters that enable the recognition of specific complexes. For instance, some other authors considered P. cearensis and P. cesarpintoi as junior synonyms of P. spilosoma. However, tests performed with material recently collected in type localities, as well as type series data, revealed some morphological characters that can be used to differentiate these species. Phylogenetic analyses with molecular data were contrasted with morphological and biogeographic data. As a result of this integrative analysis (morphology and molecular), in first chapter the validity of Parotocinclus cearensis was confirmed by differentiating it from P. spilosoma and P. cesarpintoi. The redescriptions of P. cearensis, P. cesarpintoi and P. spilosoma are presented, adding new diagnostic characters for each species. In the second chapter I addressed the relationships among species, identified possible new species, and investigated the diversification of lineages within the genus in Brazilian Northeast. I evaluated which events may be associated with the bioogeographic patterns recovered. In the third chapter, I described a new genus in the subfamily Hypoptomatinae, with four new, geographically isolated species supported by morphological and molecular data.